Investigations of thermal properties of simple van der waals crystal based nanocomposites - Stachowiak, P.; Jeżowski, A.; Nikonkov, R.; Romanova, T. (Recent Contributions to Physics, 2015)
Physical properties of the objects featuring nanometric linear dimensions have been being intense investigated for over ten years. The reason for the scientific interest is twofold:• basic science – the objects of dimensions of tens of nanometers display new physical properties, usually very much different than their macroscopic counterparts• possible applications – the new properties of such the objects make it possible to design new devices.The nanostructured materials along with their new properties utilized as a base for new technologies have recently caused an unprecedented acceleration in some of their fields.
Keywords: thermal conductivity, nanopowders, cryocrystals crystal lattice